2017
DOI: 10.1111/dmcn.13507
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related reference values for the pediatric Scale for Assessment and Rating of Ataxia: a multicentre study

Abstract: In typically developing European children, both SARA scores and interobserver agreement are age-dependent. For reliable interpretation of pediatric SARA scores, consideration of the underlying test construct appears prudent. These data will hopefully contribute to a correct and uniform interpretation of longitudinal SARA scores from childhood to adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 21 publications
5
34
0
4
Order By: Relevance
“…In children, the reliability of this method is very high (intraclass correlation coefficient=0.997) . We accounted for age‐related influences on the SARA and PBS scores by using age‐corrected SARA and PBS values. For rating scale information, an explanation of the age corrections, and age‐corrected SARA score values see Appendix S2 and Table S1 (online supporting information).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In children, the reliability of this method is very high (intraclass correlation coefficient=0.997) . We accounted for age‐related influences on the SARA and PBS scores by using age‐corrected SARA and PBS values. For rating scale information, an explanation of the age corrections, and age‐corrected SARA score values see Appendix S2 and Table S1 (online supporting information).…”
Section: Methodsmentioning
confidence: 99%
“…When the latter is due to DCD, it can be associated with other disorders such as attention‐deficit/hyperactivity disorder, and also with mildly ataxic, dystonic, or choreatic features that are not excluded from the diagnosis . Physiologically delayed motor coordination in very young children is excluded from the DCD diagnosis, since it reflects typical brain development . The underlying aetiology of DCD is still unclear, but dysfunctional activation within the cerebellar, basal ganglia, and corticospinal networks has been suggested .…”
mentioning
confidence: 99%
“…Ongoing assessment of children's physical ability and function with pCMS is also important to track progress and assist with development of their therapy program. Outcome measures that may be used include the pediatric SARA (Scale for the Assessment and Rating of Ataxia) [30,58] or BARS (Brief Ataxia Rating Scale) [57], which enable a quantification of severity of ataxia. These may be used alongside more functional and participation/quality of life measures, for example the Bruininks-Oseretsky test of Motor Proficiency 2 [6] or the Pediatric Evaluation of Disability Inventory [24].…”
Section: Rehabilitation Of Cerebellar Motor Problems During and Aftermentioning
confidence: 99%
“…Some studies have confirmed the validity of this scale for Friedreich's ataxia, spinocerebellar ataxia, and posterior fossa tumor . Although additional reports indicate that the SARA is age‐dependent and reliable in normal children, another author objected to this conclusion . In short, the SARA requires further assessments of validity and reliability.…”
Section: Behavioral Assessments Of Pmdsmentioning
confidence: 99%